2010
DOI: 10.1002/elan.201000020
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes‐Ionic Liquid and Chloropromazine Modified Electrode for Determination of NADH and Fabrication of Ethanol Biosensor

Abstract: Potential cycling was used for oxidation of chloropromazine and producing an electroactive redox couples which strongly adsorbed on the electrode surface modified with carbon nanotubes and ionic liquid nanocomposite. The modified electrode shows excellent electrocatalytic activity toward NADH oxidation. The differential pulse voltammetry detection provided high sensitivity, 0.5835 A M À1, low detection limit, 80 nM at concentration range up to 20 mM. An ethanol biosensor was also developed by immobilizing alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…The addition of LiClO 4 was to control the rate of reduction of R 16 Pc 2 Lu film. Similar spectroscopic measurements were performed on oxidized R 16 Pc 2 Lu spun films chemichromically modified by L(þ)-ascorbic acid (vitamin C) of concentrations ranging from 0.03 mM to 3.5 mM.…”
Section: Methodsmentioning
confidence: 74%
See 3 more Smart Citations
“…The addition of LiClO 4 was to control the rate of reduction of R 16 Pc 2 Lu film. Similar spectroscopic measurements were performed on oxidized R 16 Pc 2 Lu spun films chemichromically modified by L(þ)-ascorbic acid (vitamin C) of concentrations ranging from 0.03 mM to 3.5 mM.…”
Section: Methodsmentioning
confidence: 74%
“…The phthalocyanine compound R 16 using diaza(1,3)bicyclo [5.4.0]undecane as promoter. b-Nicotinamide adenine dinucleotide, reduced disodium salt (NADH of purity approx.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrode showed good stability and selectivity, and was further applied to milk powder samples with satisfactory results. Salimi et al (2010) recently have reported a new carbon nanotubes-ionic liquid and chloropromazine modified electrode (Fig.11) biosensor for determination of NADH and fabrication of Ethanol. The nanocomposite modified electrode displays excellent electrocatalytic activity toward oxidation of NADH.…”
Section: Electrochemical Biosensingmentioning
confidence: 99%